Does a caesarean affect breastfeeding initiation? Evidence among women who delivered in health facilities - Maria Gayatri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Introduction: Breastfeeding initiation is internationally recommended due to its benefits on maternal and child health. The aim of the study was to determine the relationship between mode of delivery and early breastfeeding initiation among women who delivered in health facilities. Methods: The study based on The Indonesia Demographic and Health Survey 2017. There were 5,369 women whose children born in the last 24 months preceding the survey in health facilities in Indonesia. Descriptive statistics and binary logistic regression were used for data analysis. The complex sample design was performed for analyses. Results: Of the women who had given birth to at least 24 months preceding the survey in health facilities, 57 percent was found to practice initiation breastfeeding. The likelihood of breastfeeding initiation among women who delivered in health facilities was associated with mode of delivery, which women with caesarean delivery (OR = 0.33; 95% CI: 0.29-0.38) were less likely to practice breastfeeding initiation compared with those with normal vaginal delivery after adjusted by socio-economic factors. Moreover, women age 35-49 years and non-working women were found to have higher probabilities to practice breastfeeding initiation. Conclusion: Maternal age, working status and type of delivery were significantly influencing the practice of early initiation of breastfeeding among women who delivered in health facilities. Therefore, education and promotion of breastfeeding initiation need to be improved, so couples can raise their knowledge and awareness of the benefits of breastfeeding initiation then implement it.